Efikasi Diri Peserta Didik pada Pembelajaran Sains Ditinjau dari Gender - Amalia Rahmadani; Jumadi Jumadi; Insih Wilujeng; Suyanta Suyanta; Adilah Afikah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine students’ self-efficacy in Science learning. In addition, this study also aims to determine whether there is a difference of students’ self-efficacy in Science learning according to gender. The research subjects were 34 students SMP Negeri 14 Yogyakarta consisting of 14 female students and 20 male students. The research instrument used is a questionnaire containing four indicators of self-efficacy in Science learning and 13 sub-indicators. The research analysis used is descriptive statistics and T-test. The results showed that the students' self-efficacy in Science learning is at a moderate level with a mean of 3.66. The mean in the female group is 3.68 (moderate) and the male group is 3.65 (moderate). The results of the T-test analysis showed that there is no difference in students’ self-efficacy in Science learning between groups of female and male students. The results of this study only contain a small sample, therefore it is hoped that there will be further research using a wider sample